2017
DOI: 10.1002/acr.22934
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spinal Fracture and Other Diagnoses Associated With Mortality in Hospitalized Ankylosing Spondylitis Patients

Abstract: Objective Little data exist regarding mortality in Ankylosing Spondylitis (AS). We assessed diagnoses associated with in-hospital mortality in AS using a population-based inpatient dataset. Methods Data were abstracted from the Healthcare Cost and Utilization Project- Nationwide Inpatient Sample (HCUP-NIS) between 2007–2011. We identified AS admissions using International Classification of Diseases-9 Clinical Modification (ICD9-CM) code 720.0. In-hospital mortality was the primary outcome. Logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
3
25
0
1
Order By: Relevance
“…Similarly, previous work using the Nationwide Inpatient Sample by Wysham et al found that patients with cervical spine fractures in the setting of AS had a significantly higher mortality rate. 18 In another study utilizing Nationwide Inpatient Sample, Kurucan et al found a significant association between cervical spine fractures managed operatively in patients with AS and pulmonary complications. 19 However, in the multivariable logistic regression analysis, we found that patients with a thoracic spine fracture in the setting of AS or DISH had decreased odds of having a complication or dying from the event within 1 year; the other spine regions did not show such an association.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, previous work using the Nationwide Inpatient Sample by Wysham et al found that patients with cervical spine fractures in the setting of AS had a significantly higher mortality rate. 18 In another study utilizing Nationwide Inpatient Sample, Kurucan et al found a significant association between cervical spine fractures managed operatively in patients with AS and pulmonary complications. 19 However, in the multivariable logistic regression analysis, we found that patients with a thoracic spine fracture in the setting of AS or DISH had decreased odds of having a complication or dying from the event within 1 year; the other spine regions did not show such an association.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported death in AS patients [ 26 , 33 ], and there are controversies whether AS increases the death rate. A report showed that AS does not have an effect on death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bei Patienten mit SpA können Komorbiditäten vorliegen und sollten regelmäßig diagnostiziert und therapiert werden. In der internationalen COMOSPA-Studie zur Erfassung von Komorbiditäten und ihrer Screeningstrategie bei Patienten mit SpA waren die häufigsten Komorbiditäten Osteoporose (13 %), gastrointestinale Ulzerationen (11 %) und kardiovaskuläre Erkrankungen [161].…”
Section: Komorbidität Und Mortalitätunclassified